2008
DOI: 10.1086/587840
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Primordial Non-Gaussianity on Halo Bias

Abstract: It has long been known how to analytically relate the clustering properties of the collapsed structures (halos) to those of the underlying dark matter distribution for Gaussian initial conditions. Here we apply the same approach to physically motivated non-Gaussian models. The techniques we use were developed in the 1980s to deal with the clustering of peaks of non-Gaussian density fields. The description of the clustering of halos for non-Gaussian initial conditions has recently received renewed interest, mot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
652
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 422 publications
(673 citation statements)
references
References 26 publications
21
652
0
Order By: Relevance
“…The Fourier space formalism was used by a majority of papers on non-Gaussian bias (e.g. [45,57,58,59,60]). However, an arguably more intuitive measure of the bias is in real space, where the density fluctuation in peaks (i.e.…”
Section: Biasmentioning
confidence: 99%
“…The Fourier space formalism was used by a majority of papers on non-Gaussian bias (e.g. [45,57,58,59,60]). However, an arguably more intuitive measure of the bias is in real space, where the density fluctuation in peaks (i.e.…”
Section: Biasmentioning
confidence: 99%
“…This excess power at large scale can be induced by primordial non-Gaussianity (see e.g. Matarrese & Verde 2008;Dalal et al 2008;Slosar et al 2008;Desjacques & Seljak 2010;Xia et al 2010) or exotic physics (Thomas et al 2010); however Samushia et al 2011 found that the redshift dependence of the excess power is different from what would be caused by non-Gaussianity, and Ross et al (2011) suggest that this is likely to be due to masking effects from stellar sources. After correcting for systematics, Ross et al (2012) found consistency at better than 2σ between the BOSS CMASS DR9 large-scale clustering data and the WMAP LCDM cosmological model.…”
Section: A4 Las Damas Mocksmentioning
confidence: 99%
“…Following the approach of Kaiser (1984), Matarrese & Verde (2008) also computed the effect of local-type nonGaussianity (1) on the halo two-point correlation. Drawing on earlier work by Matarrese et al (1986), who computed the n-point halo correlations by expanding the relevant pathintegrals and next resumming the series within a large-distance and rare-event approximation, they obtained expressions of the form (72) without the prefactor (1 + δ LM ) and (84) without the terms in the first line, which arise from this prefactor, and the last term f 1;11 in the second bracket.…”
Section: Bias Of Dark Matter Halosmentioning
confidence: 99%